Manual de traumatología. Cirugía traumatológica y de cuidados intensivos. (2022) - Peitzman, Andrew B; Yealy, Donald M; Fabian, Timothy C; Schwab, William; Guyette, Francis X; Seamon, Mark J
No abstract available